Study of structure transition and crystallization of amorphous silica under compression - Giap, Thi Thuy Trang (H. : ĐHQGHN, 2020)
In this work, we use molecular dynamic (MD) simulation to study the structure transition and crystallization of amorphous silica (SiO2) under compression. The structural evolution of amorphous SiO2 is explained through radial distribution function, coordination number distribution, bond angle distribution and visualization. Simulation result shown that there is a structural transformation from tetrahedral to octahedral network through SiO5 units. In the 5-15 GPa pressure range, structural transformation occurs powerfully and there are three structural phases corresponding to SiO4-, SiO5-, and SiO6- ones. At 15 GPa, octahedral-network (SiO6) is dominant. It is the first time we showed that when pressure is higher than 20 GPa, octahedral-network of amorphous SiO2 has a tendency to transform to stishovite crystalline phase.